The 2015 edition of the GEISA spectroscopic database - Jacquinet-Husson N.; Armante R.; Scott N. A.; Chédin A.; Crуpeau L.; Boutammine C.; Bouhdaoui A.; Crevoisier C.; Capelle V.; Boonne C.; Poulet-Crovisier N.; Barbe A.; et al. (2016, 2016)
Title screen